P463 Crohn's disease–associated anorectal cancer has a poor prognosis with high local recurrence: a subanalysis of the Nationwide Japanese Study. (30th January 2023) - Ogino, T; Mizushima, T; Sekido, Y; Fujii, M; Eguchi, H; Nezu, R; Ikeuchi, H; Uchino, M; Futami, K; Okamoto, K; Ajioka, Y; Sugihara, K; et al.
Abstract: Background: Cancer is the worst prognostic factor for patients with Crohn's disease (CD). Previous studies of CD-associated colorectal cancer (CRC) have involved only small numbers of patients, and no large series have been reported. The aims of this study are to clarify the prognosis and clinicopathological features of CD-CRC compared with sporadic CRC using a large nationwide database from the Japanese Society for Cancer of the Colon and Rectum. Methods: A large nationwide database covering data from 1980 to 2020 was used to identify patients with CD-CRC (n=233) and sporadic CRC (n=129, 783). The clinicopathological features, 5-year overall survival (OS), and 5-year recurrence free survival (RFS) for patients with CD-CRC were compared with these outcomes in sporadic CRC. The data were further analyzed based on tumor location in the colon (CC) or anus/rectum (RC). Propensity score (PS) matching was used to account for selection bias. A binomial logistic regression model was used to estimate the PS, using the nine effective covariates: age at cancer diagnosis, sex, CEA, surgical treatment, adjuvant chemotherapy, tumor depth, lymph node metastasis, distant metastasis, and residual tumor. Results: Compared with sporadic cases, patients with CD-CRC were younger, more often had RC, multiple lesions, and mucinous adenocarcinoma. R0 resection was less common with CD-CRC (77.43%) vs sporadic CRC (90.99%; P <0.001). Five-year OS was worse with CD-CRC vs sporadic CRC (53.99% vs 71.17%, P <0.001). Evaluation by tumor location showed significantly worse 5-year OS and RFS with CD-RC compared with sporadic RC, whereas 5-year OS and RFS in CD-CC vs sporadic CC was comparable. A higher recurrence was found with CD-RC (39.57%) compared with sporadic RC (21.97%, P <0.001), but the recurrence rates did not differ between CD-CC and sporadic CC. The most frequent sites of recurrence in CD-RC were local. Following PS matching, 5-year RFS with CD-RC was significantly worse than with sporadic RC (52.41% vs 78.74%, P< 0.001), but 5-year RFS did not differ between CD-CC and sporadic CC (81.07% vs 82.04%, P =0.900). Conclusion: Poor prognosis with CD-CRC is attributable primarily to RC and high local recurrence. Local control is indispensable to improving prognosis.